Electroconvulsive therapy induces transient sensitivity for a serotonin syndrome: a case report - Deuschle, Michael; Böhringer, Andreas; Meyer-Lindenberg, Andreas; Sartorius, Alexander (Pharmacopsychiatry, 2017)
Introduction: Serotonin syndrome is a potentially life-threatening condition with delirium, vegetative and neuromuscular symptoms as well as neural hyperexcitability. The main causes are combinations of serotonergic drugs, excessive dosages of serotonergic agents or the recreational use of certain drugs. Methods and Results: We report a case of a patient who started developing serotonin syndrome after a cumulative dose of only 900 mg lithium carbonate given in temporal association with electroconvulsive therapy (ECT). The patient tolerated the serotonergic combination of escitalopram and lithium well a few weeks after ECT. Discussion: Generally, hypersensitivity to psychotropic medications during a course of ECT is rare and hypothetically attributed to a possible and reversible alteration of the blood brain barrier. Consecutively, drugs with assumed central nervous side effects should be started at low dosages and slow titration within the first two days after ECT because even low plasma concentrations may not be tolerated. Importantly and as in other cases, the liability appeared to be of transient nature. In cases of non-tolerance immediately after ECT, a re-exposure after several weeks seems justified.